Perceptions of the technology acceptance model and the impact of mobile technology on learning in english as a foreign language classrooms: insights from students and teachers - Kartika, Nur Helida; Darmawan, I Gusti Ngurah; Susilo, Susilo; Setiawan, Iwan (Jurnal Info Sains : Informatika dan Sains, 2024)
This study utilises a mixed-method approach to analyse the impact and usage of mobile technology among Indonesian English as a Foreign Language (EFL) teachers and students. The study examines gender factors to understand their interrelation with mobile technology usage. Using online survey questionnaires and semi-structured interviews, this research explores the viewpoints of 150 English educators and 215 secondary students in Indonesia, concentrating on the Technology Acceptance Model (TAM) and Mobile Technology Impact (MTI). The findings demonstrate a clear link between TAM and MTI for both teacher and student cohorts. Male and female students typically hold similar perceptions of TAM and MTI, with the exception of the aspect of promoting collaborative learning. Female students demonstrate a more favourable outlook in this regard. In contrast, teachers uniformly perceive TAM and MTI regardless of their gender. Additionally, the promotion of collaborative learning appears as the least important factor in both Structural Equation Models (SEMs). These discoveries have implications for mobile device incorporation in English classrooms, highlighting the necessity for custom approaches to satisfy diverse perceptions and demographics.